Power Quality Analysis of Integration Photovoltaic Generator to Three Phase Grid under Variable Solar Irradiance Level - Amirullah Amirullah; Ontoseno Penangsang; Adi Soeprijanto (Universitas Ahmad Dahlan, 2016)
Objective of research is to analyze the influence of solar irradiance and integration of photovoltaic (PV) generator to power quality of three phase grid on the constant temperature and load, based on changes in some level of integration of PV generator. Power quality aspects studied are fluctuation or changing, and harmonics of voltage and current on eight scenarios PV generator connected to three-phase grid, using passive filter circuit model double band pass (double tuned). Research shows that voltage and current values on the PCC bus before use double tuned passive filter on the condition only connect single generator is still stable. However, if the PV generator connected to the three phase grid, amounted to more than one generation, voltage and current grid becomes unstable (fluctuation). At the level of solar radiation remains, the greater number of PV generators connected to the grid three-phase, then the values of voltage and current THD increases. At the level of solar irradiance increases, average THD of voltage and current grid also increased. Avarage THD of voltage and current grid is reduced after double tuned passive filter installed. Therefore, double tuned passive filter able to improve profile of voltage and current THD grid as a result of the integration of a number of PV power generators in three-phase grid according IEEE Standard 519-1992. Simulation and analysis of this research use Matlab/Simulink.